Myocardium Arrangement and Coronary Vessel Distribution in the Ventricle of Three Neotropical Freshwater Teleosts - Gardinal, Mario Vitor Buzete [UNESP]; Faccioli, Claudemir Kuhn; Chedid, Renata Alari [UNESP]; Mori, Ricardo Hideo [UNESP]; Vicentini, Irene Bastos Franceschini [UNESP]; Vicentini, Carlos Alberto [UNESP] (Zoological Society of Japan, 2018)
The ventricle of the fish heart is a chamber that exhibits great morphological and vascular variability among species. However, although the Neotropical region has the greatest taxonomic and functional diversity in freshwater fish, many considerations have been formed without previous knowledge of the ventricular morphology of these fishes. Thus, the purpose of the present study was to describe the anatomy, myoarchitecture, and distribution of coronary vessels in the ventricle of three species belonging to two representative groups from this geographical area, Leporinus elongatus, Hoplias malabaricus (Characiformes) and Pterodoras granulosus (Siluriformes), using gross anatomy and light microscopy. The species L. elongatus and H. malabaricus presented a pyramidal ventricle associated to a mixed myocardium, formed by compact and spongy layers. The mixed myocardium was also observed in P. granulosus, but associated with a sac-like ventricle. The compact layer of the species studied was formed by muscular bundles in longitudinal and circular disposition. The spongy layer constituted most of the ventricular myocardium and was formed by a complex network of trabecular sheets presenting muscle fibers also in longitudinal and circular disposition. Coronary vessels were present in the three species and were observed primarily on the surface of the bulbus arteriosus, later branching on the ventricular surface and penetrating the myocardium only at the compact layer level. These characteristics allow classification of the ventricles studied as type II. Although the type I ventricle is the most common type in teleosts, it is important to emphasize that this type has not been observed in any Neotropical freshwater teleosts studied to date.
Keywords: anatomy; heart; histology; myoarchitecture; vascularization